USE VERTUAL TEACHING TECHNOLOGIES TO TEACH MICROORGANISMS IN BIOLOGY LESSONS - S. R.Otaoev; Isaqjonova Nihola Qurbonboy qizi (Galaxy International Interdisciplinary Research Journal, 2023)
The use of vertical training technologies to teach the subject of microorganisms is the most effective teaching process. This is because there are experiments that are not part of the teaching process. Vertical experiments are conducted, such as experimenting with viruses, so using virtual education in modern-day training is the most effective teaching method. In addition, virtual learning provides distance learning. In this case, if the student is sick, he or she submits a verual assignment. He will not be left out of the classroom.